PEMBUATAN SELAI LEMBARAN TERONG BELANDA (The Making of Slice Jam from Belanda Eggplant) (Jurnal Teknologi Pangan, 2013)
The Belanda eggplant  is  one  of  multipurpose  fruit  commodity,  classified  as  a commercial commodity and has a cheap price, especially in the harvest season. The Belanda eggplant including climateric fruit have sour taste, contains many useful nutrients for health, the nutrient content of which is vitamin C, antioxidants, vitamin E, and many others. The addition of pectin and sorbitol can improve  the quality  of  physical, chemical, and organoleptic slice jam. The  research  method used Completely  Randomized Design(CRD) factorial pattern with two factors  and  three  replications.The  first  factor:  the  addition  ofpectin(0.25%, 0.50%, 0.75%, 1.00%), and  the  second  factor:  the  addition  of  sorbitol(5%, 10%, 15%, 20%). The  results showed  the  addition  of  pectin  treatment  of  0.25% and  the  addition  of  sorbitol15% yield  of acceptable slice jam consumers. The  treatment resulted  in water levels 21.169%, 28.444% antioxidant  activity,  gel  density  3.273  mm/gr.sec,  60.433% yield,  flavor  (neutral) 4.50  and texture (like) 6.67 .Key words : slice jam, Belanda eggplant, pectin, sorbitol